A Comparative Study of Prison Inmates With and Without ADHD: Which Neuropsychological and Self-Report Measures are Most Effective in Detecting ADHD Within Correctional Services?. Issue 7 (May 2023) - Etterlid-Hägg, Vanessa; Pauli, Malin; Howner, Katarina
Objective: In this study we aimed to investigate the screening and diagnostic properties of various self-report instruments to identify measures which most effectively detect ADHD in a correctional sample. Method: The sample consisted of 193 male high security prisoners in Sweden. We investigated if measures of ADHD symptoms, executive functioning, impulsivity, estimated IQ and working memory could differentiate participants with ADHD from those with ASPD or no diagnosis. Results: Participants with ADHD obtained significantly higher total scores on all included measures. Although we found that some of the measures were more efficient in differentiating ADHD, mean values were generally elevated in the sample. Conclusion: Results demonstrate the importance of investigating psychometric properties in relevant samples to assure a measurement's usefulness in different contexts, in this case a correctional setting, where the high influence of unspecific behavioral indicators in these measurements might negatively affect their validity.